2g-g-1=7

Simple and best practice solution for 2g-g-1=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g-g-1=7 equation:


Simplifying
2g + -1g + -1 = 7

Reorder the terms:
-1 + 2g + -1g = 7

Combine like terms: 2g + -1g = 1g
-1 + 1g = 7

Solving
-1 + 1g = 7

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 1g = 7 + 1

Combine like terms: -1 + 1 = 0
0 + 1g = 7 + 1
1g = 7 + 1

Combine like terms: 7 + 1 = 8
1g = 8

Divide each side by '1'.
g = 8

Simplifying
g = 8

See similar equations:

| -4y-2=-34 | | 5b=7100 | | r/9-1=15 | | -1/2b-3=9 | | 3/4(b+8)=13 | | 15-x/7=13 | | 5-4C=-3 | | 4m-3=-11 | | 4a+7=35 | | 5x=93 | | Y+2=4(x+3) | | 2h-h-1=7 | | 2+11x=32x+x | | 2y^2+3Y-35=0 | | A+BC=X | | 111-6x=21x+21 | | 1/2*2 | | -1/2y+7=-1 | | -3(n-5)-(3n-1)=-2+(7n-3) | | 3x+42=12x-40 | | 9x-11=x | | 3x+3=(-2)x-12 | | Y-4=2(x+1) | | 35z-24z=42 | | 1/4c+1-2 | | x/2-4=(-5) | | 10*-5= | | 17-(5x+3)=-16 | | 3(n+4)-2(n)=38 | | 2r-7=15 | | j/4-1=12 | | -5(n-3)-(3n-7)=-3+(3n-4) |

Equations solver categories